Increased anandamide induced relaxation in mesenteric arteries of cirrhotic rats: role of cannabinoid and vanilloid receptors - Domenicali, M (Copyright 2005 by Gut, 2005)
Background and aims: Anandamide is an endocannabinoid that evokes hypotension by interaction with peripheral cannabinoid CB1 receptors and with the perivascular transient receptor potential vanilloid type 1 protein (TRPV1). As anandamide has been implicated in the vasodilated state in advanced cirrhosis, the study investigated whether the mesenteric bed from cirrhotic rats has an altered and selective vasodilator response to anandamide. Methods: We assessed vascular sensitivity to anandamide, mRNA and protein expression of cannabinoid CB1 receptor and TRPV1 receptor, and the topographical distribution of cannabinoid CB1 receptors in resistance mesenteric arteries of cirrhotic and control rats. Results: Mesenteric vessels of cirrhotic animals displayed greater sensitivity to anandamide than control vessels. This vasodilator response was reverted by CB1 or TRPV1 receptor blockade, but not after endothelium denudation or nitric oxide inhibition. Anandamide had no effect on distal femoral arteries. CB1 and TRPV1 receptor protein was higher in cirrhotic than in control vessels. Neither CB1 mRNA nor protein was detected in femoral arteries. Immunochemistry showed that CB1 receptors were mainly in the adventitia and in the endothelial monolayer, with higher expression observed in vessels of cirrhotic rats than in controls. Conclusions: These results indicate that anandamide is a selective splanchnic vasodilator in cirrhosis which predominantly acts via interaction with two different types of receptors, CB1 and TRPV1 receptors, which are mainly located in perivascular sensory nerve terminals of the mesenteric resistance arteries of these animals.